Translation Analysis on the Transcript of Rico the Series: ‘My Father is My Hero and Special Gift’ - Anis Nurrohmah; Dini Riandini (Program Studi Diploma Tiga Bahasa Inggris Fakultas Ilmu Budaya Unsoed, 2023)
Riko the Series is an Educational animated children's series which present scientific content related to the Qur’an (Quranic Sciences) in each episode. The focus of this study is to analyze the translation of the transcript of an animated short film entitled “My Father Is My Hero and Special Gift. The method used in translating Animated Short Film Riko the Series is literature study and direct practice. The translation techniques used in this study were amplification, variation, transposition, borrowing, and literal translation. During the direct practice, the obstacles faced were the lack of vocabulary, the difficulty in finding the right diction, and the difficulty in equating the accuracy of subtitles with the timeliness of film dialogue. To overcome the obstacles the solutions were looking for terms in the target language from words that are not understood with the help of a dictionary, and learning the features contained in the Aegisub application.